Evaluación de la satisfacción laboral y su influencia en la calidad de atención al cliente en el almacén “Junical” del cantón Bolívar - Zamora Macías, Ana María (2021)
The objective of this work was to evaluate job satisfaction to identify the influence on the quality of customer service in the “JUNICAL” warehouse in Bolívar canton. Descriptive, deductive, inductive and correlation methods were used as methods that allowed the systematization of the research and contribute to the achievement of the established objectives, as well as research techniques such as: survey, interview, serqual model, cause-effect diagram, which allowed the methodological and systematic procedures in the collection of information. Likewise, this research was developed in three phases: Identification of the degree of the level of job satisfaction, determining the influence of job satisfaction and its relationship with the level of quality of customer service and proposing an action plan. As a result, it was obtained that job satisfaction in the Junical warehouse was excellent with 94%, all the dimensions evaluated reflected an optimal score, such as recognition with 97%, participation in decision making 94% and communication, satisfaction with their work , and physical conditions with 93%. Likewise, the quality of customer service was excellent with 91%, all the evaluated dimensions provided an optimal score, such as responsiveness with 93%, empathy 92%, tangible elements 91%, and with 89% reliability and security. It is concluded that job satisfaction notably influences the quality of customer service, this is corroborated by the high positive statistical correlation of 0.98 between these two variables.